A Study on Wind Pressure Characteristics of a Large-Span Membrane Structure under the Fluctuating Wind in a Vertical Direction Based on a Large Eddy Simulation - Fangjin Sun; Haoxuan Tang; Mingjin Lu; Daming Zhang; Chen Lu (Modelling and Simulation in Engineering)
This paper reports the wind pressure characteristics on long-span roofs under fluctuating wind in a vertical direction based on a large eddy simulation (LES). Three types of roofs, i.e., saddle, wavy, and continuous arch roofs, are tested. First, the membrane structure canopy is measured, and the model is established for numerical simulation. The computational models and methods are verified by comparing the obtained wind pressure distributions on the roof with the measured results and numerical simulation results under other methods. Next, a numerical simulation is performed to understand not only the wind pressure and the wind speed time series but also the wind vibration responses and fluid-solid coupling. The effects of lateral fluctuating wind at different wind speeds on the wind-induced vibration response and wind pressure distribution of different membrane structures are studied. Based on the results, the wind pressure zones of the roofs are discussed. Furthermore, the original structures are optimized and numerically simulated considering the streamlined design concept to study the influence mechanism of fluctuating wind on the roof in more detail.